Pengembangan Aplikasi Pemesanan dan Pembayaran Digital Umum UMKM Kuliner Tradisional - Suryo Sudiro; Agung Nugroho; Christian Damar S; Edy Susena (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
This article examines the case of Warung Sate Kambing in Mojosongo, Solo, with an emphasis on operational activities, business strategies, customer satisfaction, and opportunities for creating applications for digital ordering and payment. The research took a descriptive qualitative approach, applying interview, observation, and literature review techniques. The analysis of this research shows that the application of digital technology, through the creation of web-based applications and the integration of the QRIS digital creation system, can improve service efficiency and expand outreach to customers. The development process is carried out using the Waterfall method to be more organized and systematic.